Algunos fenómenos de contacto vocálico en la crítica de textos poéticos griegos - Lasso de la Vega, José (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
Ihe doctrine about the conditions in which the dífferent phcnomena of vowcl contact are realized in (ireck (prodelision, elision, crasis, synizesis) is described in thc most commonly used treaties of prosody. Nevertheless, not always do editors of Greek poetry (especíally drama) take into account the possíbilíty of admitting these phcnornena in order to explain corrupt or suspect readings. This is what thc author of this essay attem ts in order to explain 18 tragie texts. He adds up other cases of monosyllabic scansioll of groups. í, tu + vowel. This subjcct gives him cause for reexamíníg the problem of Ihe supposed «dactyl» u the trochaic tetrameter of the Comedy. whose existelice he denies.